Research at flat underlying network architecture of campus - Chu-jian LIN; Si-hai ZHANG (Tongxin xuebao)
By systematic analysis of the status quo on the campus network,via deployment of BRAS and high-density switches,we deployed a flat network core,by deployment of accounting system through a bypass way,using IPOE access technology,combined with local forwarding wireless networking,assisted with linkage logging system,we achieved a unified user access certification,and we optimized the network boundary by integrating of global security policy,strategies for Internet traffic optimization base on application protocols and the deployment of caching system.Practice shows,flat underlying network architecture improves the network performance,meets the inherent requirements of campus network,while also improves users’ experience.Flat network architecture is feasible for campus network.